2003
DOI: 10.4049/jimmunol.170.4.2022
|View full text |Cite
|
Sign up to set email alerts
|

Memory Inflation: Continuous Accumulation of Antiviral CD8+ T Cells Over Time

Abstract: CD8+ T lymphocytes play an important role in the control of intracellular pathogens during both acute and persistent infections. This is particularly true in the case of persistent herpesviruses such as human CMV, which are typified by large virus-specific CD8+ T cell populations during viral latency. To understand the origin of these populations and the factors shaping them over time, we investigated the CD8+ T cell response after murine CMV (MCMV) infection. The kinetics of the acute response were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
425
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 399 publications
(453 citation statements)
references
References 54 publications
26
425
2
Order By: Relevance
“…The localization of cells does not appear to be closely linked to the expression of the chemokine receptors CXCR3 and/or CCR5. This compares to a recent study during the memory phase of an MCMV infection, which showed a relative enrichment of MCMV-specific CD8 + T cells within the liver by a factor of 1.5 [16], compared to mean enrichments of 2.2 for CMV and 4.5 for EBV in our study. We estimate that at any time point, the total number of CMV-or EBV-specific CD8 + T cells in a normal human liver is in the order of 1×10 6 for each single specificity.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The localization of cells does not appear to be closely linked to the expression of the chemokine receptors CXCR3 and/or CCR5. This compares to a recent study during the memory phase of an MCMV infection, which showed a relative enrichment of MCMV-specific CD8 + T cells within the liver by a factor of 1.5 [16], compared to mean enrichments of 2.2 for CMV and 4.5 for EBV in our study. We estimate that at any time point, the total number of CMV-or EBV-specific CD8 + T cells in a normal human liver is in the order of 1×10 6 for each single specificity.…”
Section: Discussioncontrasting
confidence: 77%
“…However, the cells did not respond efficiently to the PHA and ionomycin treatment as a positive control to warrant analysis, which was most likely linked to an aspect of long-term cell storage. In an attempt to overcome this technical problem, we used the murine CMV (MCMV) model to analyze tetramer-specific T cell function in the liver, as previously described [16]. Using this model, we observed a strong IFN-+ production in the liver lymphocyte populations analyzed, which was comparable to that in the spleen (Fig.…”
Section: Phenotypic and Functional Analysis Of Virusspecific Cd8 + T mentioning
confidence: 91%
“…These emerged as having “effector‐memory” profiles as judged by the expression pattern of molecules such as CCR7, CD62L, CD28, CD27, and CD127 (all low) 3, 16, 17. This molecular pattern suggests homing to non‐lymphoid tissues and indeed the second feature is accumulation not only in blood and spleen where it was first noted but in many such tissues such as lung and liver, as opposed to lymph nodes 1, 3, 13. The third feature observed was maintained effector functions such as cytokine release—in contrast to exhausted CD8 + T cells 8.…”
Section: The Origins Of Memory Inflationmentioning
confidence: 94%
“…Some debate still exists as to the nature of the non‐hemopoetic cell required. An obvious site is the lymph node since this is where the cells with high proliferative capacity exist (ie, those with a central memory phenotype) and there is evidence for their reactivation (upregulation of CD69, notably in mesenteric nodes in MCMV models) 1, 3, 50. However, other data (including the adenovirus model accompanied by surgery) suggest alternatives may also exist 33.…”
Section: Mechanisms Underlying Memory Inflationmentioning
confidence: 99%
See 1 more Smart Citation